Olive tree response to potassium application under different water regimes and cultivars - Rodrigues, M.A. (2019)
Taking into account the role of potassium in plant nutrition it is poorly understood the lack of studies on olive tree response to potassium application. This paper reports the results of two field trials and two pot experiments on potassium fertilization in olive carried out from 2013 to 2017. The two field trials and one of the pot experiments were classic experiments on the plant response to the nutrient application. The second pot experiment was arranged in a factorial design with two leveis of potassium, two water regimes and two cultivars ('Cobrançosa' and 'Arbequina'). The application of potassium did not increase the growth and yield of the trees although it increased the concentration of the nutrient in the tissues. The application of potassium increased the shoot/root ratio. The potassium concentration in the roots was lower than in the aerial parts for low leveis of potassium in the soil but increased more than proportionally in the root relative to the shoot as the availability of potassium in the soil increased. These results seem to indicate that the shoots are a priority sink for K and that the roots can act as a reservoir when the soil K availability is high. lndices of plant water status and chlorophyll a fluorescence parameters were not significantly affected by K applications. Plants suffering from water stress, confirmed by índices of leaf water status and chlorophyll a fluorescence parameters, yielded less phytomass. 'Cobrançosa' appeared as a more tolerant cv. to water stress than 'Arbequina; being the former more suitable to be grown under rainfed conditions and probably more adapted to climate change.